IMPOLITENESS IN INFORMATION ACCOUNT ON INSTAGRAM - Junaidi Junaidi; Erna Januarini; Gumarpi Rahis Pasaribu (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2024)
This study aims to describe the forms of hate speech impoliteness in Instagram social media which are divided into two, namely positive impoliteness and negative impoliteness. In social media, especially on Instagram, there is a lot of impoliteness in comments. This study uses a qualitative descriptive method in the data collection process and uses advanced techniques in the form of observation and note-taking techniques. The source of the data comes from Instagram gossip accounts in the form of statuses and comment columns where the data form is impolite hate speech in comments on Instagram. Identification of the data in this study is in the form of hate speech impoliteness strategies which will be divided into two, namely positive impoliteness and negative impoliteness. Data collection techniques using the method of observing and note-taking techniques. The data analysis technique in this study uses the pragmatic equivalent method, namely the method in which the opponent or speech partner is the determining tool. The results of the analysis show that there is positive impoliteness and negative impoliteness in Instagram information accounts.